TI_GERICHTE 52.2018.244 vom 10. April 2018 , Revoca della licenza di condurre a seguito di un'infrazione commessa all'estero - TI Tribunale d'appello (2018)
Revoca della licenza di condurre a seguito di un'infrazione commessa all'estero